Examining the Link between Arginase I and Bronchial Asthma - Ashti Mohammad Amin Said; Ahmed Abdulqader Al-Naqshbandi; Yasin Kareem Amin; Rebwar Jalal Ali (Disease and Health: Research Developments Vol. 6, 2025)
Background: Asthma is a chronic lung disease that affects 300 million people worldwide. Allergic asthma is a disease of airway inflammation and hyperresponsiveness. Asthma occurs by activating IgE, a receptor that bears mast cells and basophils, and the triggering factor for this is the inhalation of an allergen when it binds to complementary IgE. And this leads to lung infiltration by eosinophils, neutrophils, then activated (M 2) macrophages and (TH2) lymphocytes, which are inflammatory triggers and all these increase mucus production, which leads to mucosal edema, smooth-muscle hyperresponsiveness, and airway hyperresponsiveness (AHR) due to exposure to e.g. histamine and methacholine. Objective: The aim of this study was to detect the arginase I (ARG I) enzyme in asthma patients, and clarify its role, in addition to examining the relationship of this enzyme with bronchial asthma. Methods: Blood samples were collected from 100 patients from Department of Medicine in Rizgary Hospital in Erbil City, in addition to intact 100 volunteers; the introduced questionnaire was filled out on the basis of type-induced asthma, duration of the disease, age of the patients, gender, family history, and allergy condition, Serum was separated to perform Enzyme-linked immunosorbent assay (ELISA) in Medical Research Center to examine the association of ARGI with bronchial asthma. By ARG activity we can measure the conversion of arginine to ornithine and urea. By using a quantitative colorimetric assay at 490 nm, employing a QuantiChrom arginase assay kit (Bioassay Systems). Results: Our results depicted the association between ARGI and bronchial asthma: based on their age, significant elevation of serum arginase level was observed in the patients \(\)81 years old, with mean value (100.16\(±\)19.77c), p-value (0.000); also the duration of asthma \(\)20 years (82.48\(±\)38.81c), p-value (0.01) were remarkably affected; this significance was found in those with types of induced asthma and with allergy condition. However non-significant difference in the frequency of abnormal serum arginase levels was observed in those patients that have a family history of asthma disease and gender of the patients. This finding demonstrated a remarkable association of ARG I in the development of asthma at p > 0.05. Conclusion: The ELISA results indicated that ARG I and bronchial asthma are remarkably correlated. Patients with asthmatic symptoms have a high level of ARG I (> 40 IU/L).